Effect of soybean oil and Tween 80 on the production of botryosphaeran by Botryosphaeria rhodina MAMB-05 - Silva, Cassiano C.; Dekker, Robert F. H.; Silva, Rui Sergio S. F.; da Silva, Maria de Lourdes Corradi; Barbosa, Aneli M. (Elsevier B.V., 2007)
The addition of soybean oil and Tween 80 was evaluated with the objective of increasing the production of botryosphaeran, an exopolysaccharide (EPS) of the (1 -> 3 ;1 -> 6)-beta-D-glucan type produced by the fungus Botowsphaeria rhodina MAMB-05. Factorial design and analysis by response surface methodology was developed to select the main factors that would affect and enhance EPS production. The optimized culture conditions were: 40g l(-1) glucose with 10ml l(-1) soybean oil, and 4.5 ml l(-1) Tween 80, during 72h cultivation at 28 degrees C (180 rpm) and initial pH 5.7. The predicted result for botryosphaeran production was 8.22 +/- 1.36 g l(-1), and compared with the experimental value of 7.74 +/- 0.13 g l(-1) . Partial characterization of the botryosphaeran produced under the optimized conditions showed one type of polysaccharide with P-glycosidic linkages containing glucose as monosaccharide. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: botryosphaeran; Botryosphaeria rhodina MAMB-05; exopolysaccharide; soybean oil; tween 80; response surface methodology